2016
DOI: 10.1002/14651858.cd003725.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for the treatment of Duchenne muscular dystrophy

Abstract: Moderate quality evidence from RCTs indicates that corticosteroid therapy in DMD improves muscle strength and function in the short term (twelve months), and strength up to two years. On the basis of the evidence available for strength and function outcomes, our confidence in the effect estimate for the efficacy of a 0.75 mg/kg/day dose of prednisone or above is fairly secure. There is no evidence other than from non-randomised trials to establish the effect of corticosteroids on prolongation of walking. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
266
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(309 citation statements)
references
References 130 publications
(60 reference statements)
3
266
0
9
Order By: Relevance
“…Although the side effect profile from GC steroids is extensive, muscle weakness and myopathy can occur in response to chronic GC steroid use and can be extremely debilitating (1). Curiously, chronic GC steroids are used to treat Duchenne muscular dystrophy (DMD), a primary muscle disease, and the use of steroids is associated with prolonged ambulation (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Although the side effect profile from GC steroids is extensive, muscle weakness and myopathy can occur in response to chronic GC steroid use and can be extremely debilitating (1). Curiously, chronic GC steroids are used to treat Duchenne muscular dystrophy (DMD), a primary muscle disease, and the use of steroids is associated with prolonged ambulation (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The added consequences of corticosteroid treatment are less clear. There is good evidence that corticosteroids can prolong the period of independent ambulation with associated improvements in muscle strength and function[66]. However, the detrimental effects of long-term corticosteroids are cumulative; with greater increases over time being reported in central adiposity, reduced stature, pubertal delay and bone fragility [67, 68].…”
Section: Clinical Considerations In the Evaluation Of Bone Health In mentioning
confidence: 99%
“…All patients diagnosed with DMD should have glucocorticoids prescribed (Level of evidence: 1A, Class of Recommendation: A) 32 . Comparisons between the natural history studies in the pre-glucocorticoid era and those after glucocorticoid therapy have demonstrated benefits in the motor function, giving longer independent gait, better core stabilization and upper limb function, prevention of spine deformities, and delaying the settlement of lower limb deformities [32][33][34][35][36][37][38][39] .…”
Section: Are Glucocorticoids Recommended For Dmd Patients?mentioning
confidence: 99%
“…Comparisons between the natural history studies in the pre-glucocorticoid era and those after glucocorticoid therapy have demonstrated benefits in the motor function, giving longer independent gait, better core stabilization and upper limb function, prevention of spine deformities, and delaying the settlement of lower limb deformities [32][33][34][35][36][37][38][39] . The use of glucocorticoids is also responsible for nonmotor benefits, particularly in preserving respiratory function, preventing cardiomyopathy, improving quality of life parameters and prolonging life itself 38,40,41 .…”
Section: Are Glucocorticoids Recommended For Dmd Patients?mentioning
confidence: 99%